Roosevelt and Stalin : portrait of a partnership - Butler, Susan 1948- (Vintage Books, 2016)
Butler explores for the first time the complex partnership during World War II between FDR and Stalin, reassessing in-depth how the two men became partners, how they shared the same outlook for the postwar world, and how they formed an uneasy but deep friendship, shaping the world's political stage from the war to the decades leading up to and into the new century